2019
DOI: 10.1097/gox.0000000000001998
|View full text |Cite
|
Sign up to set email alerts
|

10-year Follow-up of Mod Quad and Triangle Tilt Surgeries in Obstetric Brachial Plexus Injury

Abstract: Aim: To evaluate whether obstetric brachial plexus injury (OBPI) children who had mod Quad and triangle tilt surgeries maintained their recovered upper extremity functional movements over 10 years. Background: The short-term outcomes of surgery in OBPI patients are well documented. However, only a few publications with results over 10-year postoperative follow-up exist. We have previously reported the outcomes of these 2 surgeries in OBPI after 1, 2, and 5 years. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…With the development of surgery, arthroscopic surgical interventions on the shoulder joint began to be used for the treatment of abnormalities. A number of authors reported in a retrospective analysis of the treatment of children with shoulder monoparesis by shoulder arthroscopy that the criteria for the use of arthroscopy are as follows: limitation of external rotation, shoulder abduction, the initial stage of glenoid dysplasia (Water's dysplasia scale I-IV) [71]. The operation involved partial anterior capsulotomy of the shoulder joint, lengthening of the medial glenohumeral ligament, and partial tenotomy of the subscapularis muscle tendon.…”
Section: Results and Their Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of surgery, arthroscopic surgical interventions on the shoulder joint began to be used for the treatment of abnormalities. A number of authors reported in a retrospective analysis of the treatment of children with shoulder monoparesis by shoulder arthroscopy that the criteria for the use of arthroscopy are as follows: limitation of external rotation, shoulder abduction, the initial stage of glenoid dysplasia (Water's dysplasia scale I-IV) [71]. The operation involved partial anterior capsulotomy of the shoulder joint, lengthening of the medial glenohumeral ligament, and partial tenotomy of the subscapularis muscle tendon.…”
Section: Results and Their Discussionmentioning
confidence: 99%
“…Statistically, there was an improvement in the overall Mallet functional score, the average value being 18.8 ± 2.1; p ≤ 0.01 compared to the preoperative mean total Mallet score of 14.5 ± 1.2. Functional improvement was not only maintained for a long period, but also improvedthe average total Mallet score (20.35 ± 2.3; p ≤ 0.01) [71,72]. In 2015, a meta-analysis was carried out on the use of derotation osteotomy of the shoulder in comparison with the «Triangle Tilt» technique.…”
Section: Results and Their Discussionmentioning
confidence: 99%
“…These results supported the hypothesis that untreated obstetric brachial plexus injury could have a sustained, progressive adverse effect on limb growth-and that surgical intervention for obstetric brachial plexus injury could improve limb growth potential. Shortness of more than 5 cm, which may develop due to deficiencies in treatment modalities, can reduce the quality of life, both cosmetically and functionally [35,36]. In the treatment of this limb shortness, treatments such as the Ilizarov method, which are used in the treatment of lower extremity shortness, could be applied.…”
Section: Discussionmentioning
confidence: 99%